Sexual and reproductive health protective factors among adolescents with child welfare involvement. (September 2022) - Combs, Katie Massey; Cook Lee, Mackenzie; Ramseyer Winter, Virginia; Taussig, Heather
Highlights: About one-third (35%) of participants reported ever receiving education or information on birth control, and less than half (42%) reported knowing how to access these services if they wanted. Still, youth reported protective sexual and reproductive health (SRH) attitudes; specifically, high confidence in their ability to avoid sex when not desired, strong peer norms for condoms, and few perceived benefits to unprotected sex. Gender and age had the strongest associations with birth control knowledge and SRH attitudes; males (compared to females) and adolescents 12- to 13-years-old (compared to 14- to 15-years-old) reported less birth control knowledge and fewer protective attitudes. Though research documents a host of SRH risk for youth with child welfare involvement, this sample also possessed substantial SRH protection. Interventions, services, and professionals can help youth navigate a healthy adolescence by building upon the protective attributes that youth already possess and by bridging barriers to SRH services and education. Abstract: Youth with child welfare involvement experience disproportionate rates of sexual and reproductive health (SRH) risks and adverse outcomes. However, little is known about SRH protective factors among youth with child welfare involvement. This study examined whether birth control knowledge or SRH agency, norms, and expectancies differed by gender, age, race/ethnicity, or out-of-home care status among 245 youth, ages 12–15, with open child welfare cases due to maltreatment. Less than half of participants had received information on birth control or knew how to access birth control services; however, the majority reported high confidence in avoiding sex when not desired, strong peer norms for condoms, and few perceived benefits to unprotected sex. Males and younger adolescents had fewer protective attitudes and birth control knowledge, while Latinas had more protective attitudes. This study highlights the protective SRH attitudes already held by youth (ages 12–15) with child welfare involvement, as well as the need for early and gender-inclusive SRH education.